Yield and soil impacts of pasture renovation methods in an australian subtropical grazing system - A.J. Gibson; M.J.DuV. Gout; N.M. Sutherland; L. Kearney; T.J. Rose (Soil and Tillage Research, 2025)

Migration patterns and changes in population biology associated with the worldwide spread of the oilseed rape pathogen Leptosphaeria maculans - A. DILMAGHANI; P. GLADIEUX; L. GOUT; T. GIRAUD; P. C. BRUNNER; A. STACHOWIAK; M.‐H. BALESDENT; T. ROUXEL (Molecular Ecology, 2012)
Pathogen introductions into novel areas can lead to the emergence of new fungal diseases of plants. Understanding the origin, introduction pathways, possible changes in reproductive system and population size of fungal pathogens is essential in devising an integrated strategy for the control of these diseases. We used minisatellite markers to infer the worldwide invasion history of the fungal plant pathogen Leptosphaeria maculans , which causes stem canker (blackleg) of oilseed and vegetable brassicas. Clustering analyses partitioned genotypes into distinct populations corresponding to major geographic regions, along with two differentiated populations in Western Canada. Comparison of invasion scenarios using Approximate Bayesian Computation suggested an origin of the pathogen in the USA, the region where epidemics were first recorded, and independent introductions from there over the last few decades into Eastern Canada (Ontario), Europe and Australia. The population in Western Canada appeared to be founded from a source in Ontario and the population in Chile resulted from an admixture between multiple sources. A bottleneck was inferred for the introduction into Western Canada but not into Europe, Ontario or Australia. Clonality appeared high in Western Canada, possibly because environmental conditions there were less conducive to sexual reproduction. Leptosphaeria maculans is a model invasive pathogen with contrasting features in different regions: shallow population structure, high genetic variability and regular sexual recombination in some regions, by comparison with reduced genetic variability, high rates of asexual multiplication, strong population structure or admixture in others.